Laboratório de Ensino de Matemática: uma extensão da sala de aula - Cruz, Rodrigo Prata Santos da [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This work has as purpose to present some boardings that assist in the process of mathematics teach-learning. We detach the Laboratory of Education of Matemática (LEM) and its main components. On the basis of the National Curricular Parameters, we display four activities that had been developed and applied in a Municipal School of the Public Net of Education in the city of Roseira. In the activities the mental arithmetic is developed, to study the elementary operations and concepts of horizontal segment and vertical segment. The results show that, with the development of the activities, as much the researcher as the teacher and its pupils had been more interested in arguing, teaching and to learn mathematics

Este trabalho tem como finalidade apresentar algumas abordagens que auxiliem no processo de ensino-aprendizagem de matemática. Destacamos o Laboratório de Ensino de Matemática (LEM) e seus principais componentes. Com base nos Parâmetros Curriculares Nacionais, expomos quatro atividades que foram desenvolvidas e aplicadas em uma Escola Municipal da Rede Pública de Ensino na cidade de Roseira. Nas atividades desenvolve-se o cálculo mental, para estudarmos as operações elementares e conceitos de segmento horizontal e segmento vertical. Os resultados mostram que, com o desenvolvimento das atividades, tanto o pesquisador como a professora e seus alunos ficaram mais interessados em discutir, ensinar e aprender matemática
Keywords: Matemática - Estudo e ensino; Aprendizagem; Jogos em educação matematica; Laboratórios de matemática; Laboratory of Education of Mathematics; Educative Material